System-wide effects of hospital payment scheme reforms: The German introduction of diagnosis-related groups - Robert Messerle; Jonas Schreyögg (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2022)
Hospitals account for 40 % of all healthcare expenditures and play a central role in healthcare provision. Therefore, the way hospitals are payed has major implications for the care they provide. Yet the knowledge about system wide effects of payment reforms is surprisingly thin. This study analyzes the especially comprehensive German introduction of diagnosis-related groups. In Germany, diagnosis-related groups function as sole pricing, billing and budgeting system and almost exclusively determine the turnover of hospitals. The introduction of diagnosis-related groups thus completely overhauled existing payment structures. It thereby offers a unique possibility for the analysis of payment reforms. Using aggregate OECD data and recent econometric advances, we analyze hospital activity and efficiency. We find that the reform increased hospital activity - measured as the number of discharges - significantly by around 2 percent per year. In contrast to many earlier studies, we find that diagnosis-related groups do not necessarily lead to a lowering of the average length of stay.
Keywords: 330; DRG-System; Krankenhausfinanzierung; Krankenhaus; Gesundheitsversorgung; Deutschland